2004
DOI: 10.1103/physrevlett.93.250403
|View full text |Cite
|
Sign up to set email alerts
|

Creating a Stable Molecular Condensate Using a Generalized Raman Adiabatic Passage Scheme

Abstract: We study the Feshbach resonance assisted stimulated adiabatic passage of an effective coupling field for creating stable molecules from atomic Bose condensate. By exploring the properties of the coherent population trapping state, we show that, contrary to the previous belief, mean-field shifts need not to limit the conversion efficiency as long as one chooses an adiabatic passage route that compensates the collision mean-field phase shifts and avoids the dynamical unstable regime.PACS numbers: 03.75. Mn, 05.3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
154
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(157 citation statements)
references
References 27 publications
2
154
0
1
Order By: Relevance
“…The terms proportional to χ ′ i,j describe s-wave collisions between these species. We remark that trimer formation via an atom-dimer resonance is actively studied in ongoing experiments, and that the Feshbachresonance-aided photoassociation considered here could also be reformulated as a laser frequency modulation scheme [9,15]. Finally, the Bose-enhanced selectivity of dissociation channels in coherent photodissociation of the heteronuclear trimers ABC was also studied by Moore and Vardi [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The terms proportional to χ ′ i,j describe s-wave collisions between these species. We remark that trimer formation via an atom-dimer resonance is actively studied in ongoing experiments, and that the Feshbachresonance-aided photoassociation considered here could also be reformulated as a laser frequency modulation scheme [9,15]. Finally, the Bose-enhanced selectivity of dissociation channels in coherent photodissociation of the heteronuclear trimers ABC was also studied by Moore and Vardi [7].…”
mentioning
confidence: 99%
“…The maintenance of dark or unpopulated trimer state is important for an efficient conversion even with a very short molecular lifetime [15]. For ψ b (0) = ψ ab (0) = 0, Eqs.…”
mentioning
confidence: 99%
“…Evidently, the success of these applications depends on our ability to avoid the unstable regimes of the CPT state. For example, high efficiency coherent population transfer between the atomic and molecular condensate using STIRAP can only be achieved if these unstable regimes are not encountered during the transfer process [23]. With this in mind, we believe that our work will have important implications in the coupled atom-molecule condensates [7], a system of significant current interest, with ramifications in other nonlinear systems.…”
Section: Discussionmentioning
confidence: 97%
“…It was generally believed that the nonlinear phase shifts arising from particle collisions would defeat the two-photon resonance condition [13,15], a prerequisite for the existence of CPT states and hence the key for the successful implementation of STIRAP. In a recent work [23], we have shown that by appropriately chirping the optical frequency and the Feshbach detuning, the collision-induced nonlinear phase shifts can be dynamically compensated, hence generalizing the concept of the CPT state from the collisionless limit [13] to situations where collisions cannot be ignored. In addition, we have also shown that collisions may lead to dynamical instabilities in the nonlinear CPT state, in contrast to the CPT states in the linear Λ-system which are always stable.…”
Section: Figmentioning
confidence: 99%
“…However, understanding new kinds of systems will require the investigation of the effects of additional interactions, since Bose-Einstein condensation of molecules has now been observed using new techniques for creating ultracold molecules [5]. In addition, Ling et al [6] proposed an efficient method to convert atomic condensates into stable molecules using a generalized Raman adiabatic passage scheme. Very recently, the generation of a BEC in a gas of 52 Cr atoms was reported [7].…”
Section: Introductionmentioning
confidence: 99%